Incongruencies between phonological theory and phonetic measurement. Issue 1 (February 2020) - Mücke, Doris; Hermes, Anne; Tilsen, Sam
Abstract : To assess a phonological theory, we often compare its predictions to phonetic observations. This can be complicated, however, because it requires a theoretical model that maps from phonological representations to articulatory and acoustic observations. In this study we are concerned with the question of how phonetic observations are interpreted in relation to phonological theories. Specifically, we argue that deviations of observations from theoretical predictions do not necessitate the rejection of the theoretical assumptions. We critically discuss the problem of overinterpretation of phonetic measures by using syllable coordination for different speaker groups within Articulatory Phonology. It is shown that surface variation can be explained without necessitating substantial revision of the underlying phonological theory. These results are discussed with respect to two types of interpretational errors in the literature. The first involves the proliferation of phonological categories in order to accommodate variation, and the second the rejection of a phonological theory because the model which generates its predictions is overly simplified.